2023
DOI: 10.36660/abc.20220606
|View full text |Cite
|
Sign up to set email alerts
|

Papel do Jejum Intermitente e da Dieta Restrita em Carboidratos na Prevenção de Doenças Cardiovasculares em Pacientes Pré-Diabéticos

Abstract: Fundamentos: Pacientes pré-diabéticos têm alto risco de doenças cardiovasculares e complicações microvasculares e macrovasculares. O Jejum Intermitente (JI) e a dieta restrita em carboidratos (dieta low-carb, DLC) são estratégias dietéticas promissoras nesse grupo. Objetivos: Analisar os benefícios da combinação do JI com DLC sobre desfechos microvasculares e macrovasculares em pacientes pré-diabéticos. Métodos: O estudo incluiu 485 pacientes pré-diabéticos sem história de doença cardiovascular. Os pacientes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Thus, it was suggested that longer and larger studies are highly required to verify the differences between the group focused on body weight and the group evaluating blood glucose [ 33 ]. Lastly, Khalfallah et al examined the efficacy of both IF and low-carb diet (LCD) on microvascular and macrovascular outcomes in prediabetic patients [ 34 ]. This study demonstrated a significantly greater reduction in body weight, BMI, waist circumference, and fat percentage in group I (IF–LCD); however, no significant difference in visceral fat or skeletal muscle percentage between the two groups was noted [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it was suggested that longer and larger studies are highly required to verify the differences between the group focused on body weight and the group evaluating blood glucose [ 33 ]. Lastly, Khalfallah et al examined the efficacy of both IF and low-carb diet (LCD) on microvascular and macrovascular outcomes in prediabetic patients [ 34 ]. This study demonstrated a significantly greater reduction in body weight, BMI, waist circumference, and fat percentage in group I (IF–LCD); however, no significant difference in visceral fat or skeletal muscle percentage between the two groups was noted [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Diversos desses estudos constataram que o JI resultou em emagrecimento após a intervenção com a realização do jejum intermitente, em suas diferentes modalidades (Carter et al, 2018. Corley et al, 2018Khalfallah et al, 2023;Schroderet al, 2021).…”
Section: Schroder Et Al 2021unclassified
“…Therefore, there is a growing interest in exploring lifestyle interventions [4,16,17], such as intermittent fasting (IF), as an effective approach in managing T2DM risk parameters [18][19][20][21][22][23][24][25][26][27]. IF involves periods of reduced or no caloric intake alternated with periods of normal or increased caloric intake.…”
Section: Introductionmentioning
confidence: 99%